Demographic Profile of Blindness in Patients attending Tertiary Eye Care Centre in Central India - Bhavna Sharma; Rachna Gupta; Reena Anand; Mukesh Rajput (International Journal of Medical Research and Review, 2013)
Introduction: Blindness is a social curse & more than 80% cases of blindness are due to avoidable causes. In India greater part of blind population resides in rural area, because they often get very late medical attention for ocular problem due to varied reasons like poverty, ignorance and less availability of Medical care.Methods: This study was done to evaluate the recent epidemiological trends, clinical profile in blind patients & causes of blindness in patients attending a tertiary eye care centre of central India .Other references for evaluation were - associated risk factors in causation of blindness, management strategy for blindness & to evaluate rehabilitation services for blind patients.Results: In our study maximum no of blind patients were from rural area. Maximum numbers of Patients were from Lower class (67.8 %) followed by Middle class (26.8%). 38.4 % of blind patient were farmer by occupation followed by labourer in 24.1% of patients. 31.6 % of total blind were illiterate. 53 % were male and 47 % were female.Conclusion: The higher prevalence in the rural areas is possibly related to less availability of eye care services in these areas compared with the urban area.